Pengendalian Pembangunan Rumah Tanpa Izin di Pinggir Sungai - Iqbal A’zhmi; Muhammad Fauzan; Andin Hermawan; Muhammad Ziddan Hidayat; M Abdul Qadir Al Khair (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
The construction of houses in river border areas is a complex issue involving legal, environmental, and spatial planning aspects. River borders are protected zones designated to maintain the ecological function of rivers and to mitigate disaster risks. In Indonesia, development in these areas is regulated through various legal instruments, including Government Regulation No. 38 of 2011 and the OSS RBA (Online Single Submission Risk-Based Approach) system. Local governments play a strategic role in spatial planning, granting permits, conducting supervision, and enforcing the law. However, significant challenges persist, such as inadequate spatial data, weak integration between local and central information systems, and socio-political pressures that influence decision-making. Furthermore, overlapping authorities between central and local governments after the Omnibus Law have further complicated the permitting and monitoring processes. A case study in Tanah Laut Regency reveals that negligence in issuing permits can lead to environmental degradation. Therefore, cross-sector collaboration, strengthened human resource capacity, and policy harmonization between central and local governments are essential. The implementation of a fair, transparent, and risk-based permitting system is key to protecting river border zones and achieving sustainable development that aligns with public interests and environmental preservation.